Effect of Auxins on the Accumulation of Alkaloids in Ungrafted Annona emarginata (Schltdl.) H. Rainer and Annona emarginata (Schltdl.) H. Rainer Grafted with Annona atemoya Mabb. - Mimi, Carolina Ovile [UNESP]; De-la-Cruz-Chacón, Iván; da Silva, Felipe Moura Araujo; Roberto, Victor Cauan Rocha [UNESP]; Ferreira, Gisela [UNESP] (MDPI, 2025)
Plant regulators, such as auxins, modulate the synthesis of specialized metabolites and aid in the bioprospection of molecules. Annona emarginata is known to produce antifungal alkaloids and serves as a rootstock for Annona atemoya. This study evaluated the effects of indoleacetic acid (IAA), indolebutyric acid (IBA), and naphthaleneacetic acid (NAA) applications on the accumulation of alkaloids in ungrafted A. emarginata and grafted with A. atemoya. Total alkaloids were analyzed by spectrophotometry, and alkaloid profiles were analyzed by DI-MS at 8, 14, and 20 days after treatments (DAT). The results indicated that IAA and NAA had the strongest effects on increasing the synthesis of alkaloids in the roots of ungrafted seedlings. In grafted plants, IBA had a more pronounced effect on roots; however, at final evaluation, all three auxins had an impact on both roots and leaves. Chemometric analysis revealed that auxins also altered the alkaloid composition in both seedling types. Nineteen alkaloids were identified regardless of treatment and harvest time. Eight alkaloids were identified for the first time in A. emarginata and nine were identified in A. atemoya. The main alkaloids found in ungrafted seedlings treated with IAA, IBA, and NAA were liriodenine and lanuginosine. In grafted seedlings, liriodenine and reticuline were the primary alkaloids found in roots, whereas liriodenine, lanuginosine, and reticuline were significantly present in leaves. The use of auxins to enhance alkaloid biosynthesis demonstrates their potential for bioprospection and the development of crops tolerant to biotic stress.